2015
DOI: 10.1177/1074248415575963
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ivabradine in Cardiac Rehabilitation in Patients With Recent Coronary Artery Bypass Graft

Abstract: Adding ivabradine to low-dose bisoprolol during cardiac rehabilitation in patients with CABG improved functional capacity, enhanced recovery of systolic function, and reduced diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…These findings correspond with a meta-analysis of 41 trials of people with CHD and heart failure which found a pooled MD of 3.3 ml/kg/min for VO 2 in favour of CR32 (corresponding to ~1.0 METs). It would take a typically deconditioned cardiac patient with AF with a peak VO 2 value of ~13 ml/kg / min to a value >14 ml/kg/min 33 34. This is clinically meaningful as it would reduce the mortality and morbidity risk of such a patient35 and represents an absolute change of 4%–5% which would be noticeable in terms of associated symptoms, for example, dyspnoea.…”
Section: Discussionmentioning
confidence: 99%
“…These findings correspond with a meta-analysis of 41 trials of people with CHD and heart failure which found a pooled MD of 3.3 ml/kg/min for VO 2 in favour of CR32 (corresponding to ~1.0 METs). It would take a typically deconditioned cardiac patient with AF with a peak VO 2 value of ~13 ml/kg / min to a value >14 ml/kg/min 33 34. This is clinically meaningful as it would reduce the mortality and morbidity risk of such a patient35 and represents an absolute change of 4%–5% which would be noticeable in terms of associated symptoms, for example, dyspnoea.…”
Section: Discussionmentioning
confidence: 99%
“…Once CVR has been initiated and adequate adherence has been achieved, some patients may require dose reduction or even discontinuation of some drugs due to adaptations to physical training, e.g., patients who develop hypotension, marked bradycardia, or symptomatic hypoglycemia. 74,75…”
Section: Integration Of Cardiovascular Rehabilitation Into Optimized mentioning
confidence: 99%
“…Results indicated a significant improvement in LVEF within the combination group, escalating from 57% ± 3% at admission to 62% ± 4% at discharge, and reaching 66% ± 3% at three months. Conversely, LVEF remained relatively stable in the bisoprolol group, documented at 57% ± 3% at admission, 59% ± 4% at discharge, and 59% ± 3% at three months [16] .…”
Section: Discussionmentioning
confidence: 87%